Chlorophyll f distribution and dynamics in cyanobacterial beachrock biofilms. Issue 6 (15th September 2016) - Trampe, Erik; Kühl, Michael
Abstract : Chlorophyll (Chl) f, the most far‐red (720–740 nm) absorbing Chl species, was discovered in cyanobacterial isolates from stromatolites and subsequently in other habitats as well. However, the spatial distribution and temporal dynamics of Chl f in a natural habitat have so far not been documented. Here, we report the presence of Chl f in cyanobacterial beachrock biofilms. Hyperspectral imaging on cross‐sections of beachrock from Heron Island (Great Barrier Reef, Australia), showed a strong and widely distributed signature of Chl f absorption in an endolithic layer below the dense cyanobacterial surface biofilm that could be localized to aggregates of Chroococcidiopsis‐like unicellular cyanobacteria packed within a thick common sheath. High‐pressure liquid chromatography‐based pigment analyses showed in situ ratios of Chl f to Chl a of 5% in brown‐pigmented zones of the beachrock, with lower ratios of 0.5% in the black‐ and pink‐pigmented biofilm zones. Enrichment experiments with black beachrock biofilm showed stimulated synthesis of Chl f and Chl d when grown under near‐infrared radiation (NIR; 740 nm), with a Chl f to Chl a ratio increasing 4‐fold to 2%, whereas the Chl d to Chl a ratio went from 0% to 0.8%. Enrichments grown under white light (400–700 nm) produced no detectable amounts of either Chl d or Chl f . Beachrock cyanobacteria thus exhibited characteristics of far‐red light photoacclimation, enabling Chl f ‐containing cyanobacteria to thrive in optical niches deprived of visible light when sufficient NIR is prevalent.